2017
DOI: 10.1097/nmd.0000000000000554
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for Spiritually Oriented Cognitive Processing Therapy for Moral Injury in Active Duty Military and Veterans With Posttraumatic Stress Disorder

Abstract: Wartime experiences have long been known to cause ethical conflict, guilt, self-condemnation, difficulty forgiving, loss of trust, lack of meaning and purpose, and spiritual struggles. “Moral injury” (MI) (also sometimes called “inner conflict”) is the term used to capture this emotional, cognitive, and behavioral state. In this article, we provide rationale for developing and testing Spiritually Oriented Cognitive Processing Therapy, a version of standard cognitive processing therapy for the treatment of MI i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
91
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(92 citation statements)
references
References 60 publications
1
91
0
Order By: Relevance
“…Our results align with this notion and demonstrate that members exposed to PMIEs show a greater tendency to seek help from religious/spiritual advisors. Considering that MI is frequently linked to spiritual distress (Drescher & Foy, 2008;Koenig et al, 2017), it is not surprising that there are calls to further learn from chaplains' understanding of MI and integrate their services into the mental care provided to military members Worthington & Langberg, 2012). We found that help-seeking among members with PMIE is greater primarily for what are traditionally seen as gatekeepers (for mental health care access) such as family doctors, religious advisors, and CFMAP.…”
Section: Discussionmentioning
confidence: 76%
“…Our results align with this notion and demonstrate that members exposed to PMIEs show a greater tendency to seek help from religious/spiritual advisors. Considering that MI is frequently linked to spiritual distress (Drescher & Foy, 2008;Koenig et al, 2017), it is not surprising that there are calls to further learn from chaplains' understanding of MI and integrate their services into the mental care provided to military members Worthington & Langberg, 2012). We found that help-seeking among members with PMIE is greater primarily for what are traditionally seen as gatekeepers (for mental health care access) such as family doctors, religious advisors, and CFMAP.…”
Section: Discussionmentioning
confidence: 76%
“…Until recently, the construct of moral injury has been primarily elaborated within the field of psychology. However, the understanding of such moral issues may also be advanced through religious/spiritual lenses and served by religious/spiritual caregivers, sometimes in collaboration with clinicians (Bobrow et al 2013;Koenig et al 2017;Wortmann et al 2017). Researchers even suggest that this concept may be a new name for something that has been addressed by caregivers within wisdom traditions throughout history (Lindsay et al 2016).…”
mentioning
confidence: 99%
“…The MI Symptoms Scale is a 54-item multidimensional measure that assesses symptoms of moral injury, and is composed of 10 subscales: guilt, shame, violation of moral values, self-condemnation, betrayal by others, loss of trust, difficulty forgiving, loss of meaning, purpose and hope, spiritual struggles, and loss of faith (Harold G Koenig et al, 2017). We have recently shown in a multicenter study in veterans and active duty military the reliability and validity of this multi-dimensional symptom measure of moral injury that can be used in studies targeting MI in veterans and active duty military personnel with PTSD symptoms, and may also be used by clinicians to identify those at risk (H. G. Koenig et al, 2017). The guilt subscale consists of two items taken from the Moral Injury Questionnaire (MIQ) (Currier, Holland, Drescher, & Foy, 2015) and three items from the Combat Guilt Scale (CGS) (Henning & Frueh, 1997) (standardized Cronbach's alpha in the present sample=0.41).…”
Section: Questionnairementioning
confidence: 99%
“…Litz and colleagues (2009) define it as "perpetrating, failing to prevent, bearing witness to, or learning about acts that transgress deeply held moral beliefs." MI, a construct that is distinct from PTSD, has often been identified in those with PTSD, and may contribute to the onset and maintenance of PTSD (Dokoupil; H. G. Koenig et al, 2017). While PTSD is believed to be a chronic emotional and physical response to fear and danger, with hyper-alertness and physiological arousal, which can be triggered by reminders of the trauma, MI does not necessarily involve fear-based stressors (Nieuwsma et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation